Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.gpb.2022.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomic Analysis Reveals the Cellular Heterogeneity of Mesenchymal Stem Cells

Abstract: Ex vivo-expanded mesenchymal stem cells (MSCs) have been demonstrated to be a heterogeneous mixture of cells exhibiting varying proliferative, multipotential, and immunomodulatory capacities. However, the exact characteristics of MSCs remain largely unknown. By single-cell RNA sequencing of 61,296 MSCs derived from bone marrow and Wharton’s jelly, we revealed five distinct subpopulations. The developmental trajectory of these five MSC subpopulations was mapped, revealing a differentiation path from stem-like a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 85 publications
1
26
0
Order By: Relevance
“…Since CD106 (VCAM-1) is an adhesion molecule that facilitates interactions with vascular endothelium, we combined these markers with VCAM-1 given the perivascular location of HSC niche cells in murine models, and because previous work showed that enrichment with VCAM-1 within CD271+ BM-MSCs identifies self-renewing cells 21 . Importantly, single cell analysis of CD271+ MSCs has identified similar functional subsets within the MSC population as those we have identified here [38][39][40][41] .…”
Section: Discussionsupporting
confidence: 71%
“…Since CD106 (VCAM-1) is an adhesion molecule that facilitates interactions with vascular endothelium, we combined these markers with VCAM-1 given the perivascular location of HSC niche cells in murine models, and because previous work showed that enrichment with VCAM-1 within CD271+ BM-MSCs identifies self-renewing cells 21 . Importantly, single cell analysis of CD271+ MSCs has identified similar functional subsets within the MSC population as those we have identified here [38][39][40][41] .…”
Section: Discussionsupporting
confidence: 71%
“…Population and single-cell mRNA sequencing have demonstrated that both inter- and intra-tissue heterogeneity, gene expression, signaling pathway activation, and differentiation potentials of MSCs are exceptionally diverse, and serve the needs of the differentiated organs [ 12 , 47 , 48 ]. Single-cell transcriptomic sequencing of bone marrow and umbilical cord Wharton’s jelly MSCs revealed five distinct subpopulations that differentiate from stem-like active proliferative cells (APCs) [ 49 ]. These subpopulations express the perivascular mesodermal progenitor markers chondroitin sulfate proteoglycan 4 (CSPG4)/melanoma cell adhesion molecule-MUC18 (MCAM)/nestin (NES) of multipotent progenitor cells [ 49 ].…”
Section: Normal Tissue Fibroblastsmentioning
confidence: 99%
“…Single-cell transcriptomic sequencing of bone marrow and umbilical cord Wharton’s jelly MSCs revealed five distinct subpopulations that differentiate from stem-like active proliferative cells (APCs) [ 49 ]. These subpopulations express the perivascular mesodermal progenitor markers chondroitin sulfate proteoglycan 4 (CSPG4)/melanoma cell adhesion molecule-MUC18 (MCAM)/nestin (NES) of multipotent progenitor cells [ 49 ]. Subsequently, they branch off into either adipogenesis or osteochondrogenesis and differentiate into unipotent prechondrocytes specifically expressing immunomodulatory genes able to suppress activated CD3 + T cell proliferation [ 49 ].…”
Section: Normal Tissue Fibroblastsmentioning
confidence: 99%
“…Studies using single-cell RNA-seq have shown that MSCs are a heterogeneous population containing pre-MSCs and lineage committed MSCs [35][36][37]. Hence, the effect of environmental factors, including heat, on MSCs transcriptome and function is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%